The association between music preferences and psychiatric problems in adolescents [Ergenlerde müzik tercihi ile psikiyatrik sorunlar arasındaki İlişki] - (:unkn) unknown (Marmara University, 2012)
Despite the well-known importance of music in adolescent life, the relationship between music preferences and the psychological profiles of adolescents has not been completely clarified. The preference for some music types, especially heavy metal and rap (heavy music types), has been found to be associated with depressive symptoms, antisocial behavior and alcohol/drug usage. The lyrics of these music types and music videos also appear to contribute to these conditions. Although the bidirectional relationship between music preferences and psychiatric problems has not been well understood, the available research data suggest that the preferred music type represents already existing behavioural tendencies and emotional vulnerability towards psychiatric problems. © Marmara Medical Journal, Published by Galenos Publishing.
Keywords: Adolescents; Heavy metal; Music preference; Rap